'Soft' amplifier circuits based on field-effect ionic transistors. Issue 24 (28th June 2015) - Boon, Niels; Olvera de la Cruz, Monica
<x xml:space="preserve">Abstract</x> We demonstrate using numerical simulations and theory that Field Effect ionic Transistors (FEiT), in which ion currents are gated inside soft materials, can be used as voltage amplifiers or in building logical circuits.